#TITLE_ALTERNATIVE# - S. REYNOLD (NIM 250 03 201); Pembimbing : Dr. Ir. Herlin D. Setio , MONANG
In the construction of the first modern cable stayed bridges, only a large spacing and limited number of stays was generally used to support the rigid decks. For example, Stromsund Bridge in Sweden and Morandis Lake Maracaibo Bridge in Venezuela have only one and two cables on either side of a central pylon. Further, advance the development of stayed bridges in cable technology and analysis technique characterized by spacing cable relatively close together. Construction of the Friedrich Ebert Bridge in Bonn was the first structure containing a large number of cables. The trend of modem cablestayed bridge now is a large number of cables and spaced relatively close together. The analysis of cablestayed bridge with variation of spacing stayed cable consists of static and dynamic analysis. Static analysis is performed for variation of force in load-bearing element (deck, cable, and pylon), and dynamic analysis is used for calculation of structure stability. Variation of spacing stayed cable changes the stiffness of structure, which needs a suitable dimension of cable, deck, and pylon. There are two idealization models of the bridge structure. Plane model represents the structure to determine dimension and initial force of cable under permanent loading, and space frame model represents the structure to analyze bridge behavior under traffic loading. Even a large spacing of cables seems elegant, but technically, behavior of cablestayed bridge is much better using a closed spacing of cables. The significant advantages of cablestayed bridge with closed cable spacing are decreasing deck bending moment and normal force, distributing cable axial force uniformly, and increasing stability of structure.